APLIKASI SINKRONISASI DATABASE ANTARA SIAK STIKOM DINAMIKA BANGSA JAMBI DENGAN PdDikti - Agus Siswanto; Abdul Rahim (LPPM Universitas Dinamika Bangsa, 2017)
STIKOM Dinamika Bangsa Jambi is one of the computer colleges in the city of Jambi. Currently STIKOM Dinamika Bangsa Jambi already has an academic information system that is processed by the BAAK. As with private universities in general, every semester of the academic process should be reported to their respective Kopertis Region. Problems that arise is the process of inputting data that is repeated data that has been inputted to the application of academic information system will insert again to be reported using application feeder PDDIKTI (Pangkalan Data Pendidikan Tinggi). Application of Web Service Technology To Integrate Basisdata Academic Information System Stikom Dinamika Bangsa Jambi With Basisdata Feeder Pangkalan Data Pendidikan Tinggi (PDDikti) can be utilized to solve existing problems in data entry activities in STIKOM Dinamika Bangsa Jambi.